THE HABIT OF READING PICTURE STORY BOOKS IN IMPROVING THE LINGUISTIC INTELLIGENCE OF ELEMENTARU SCHOOL STUDENTS - Basyar Salim; Izzatul Muslimah; Wahyuni Nur Ammala; Junia Saptaningrum; Conny Dian Sumadi (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The level of reading skills is very closely related to the level of students' linguistic intelligence. One way to improve reading skills is to make reading activities a habit. This study aims to determine the effect of reading habit before learning with the aid of picture story books to improve the linguistic intelligence of second grade students of SD N Duduwetan. This type of research is descriptive qualitative with data collection techniques namely observation, interviews and documentation. The research instrument is a guide observation sheet and interviews with data analysis techniques in the form of data reduction, data presentation and data verification. The results of this study indicate that the level of reading skills obtained are 3 students with low skill levels, 4 students with medium skill levels and 4 students with high skill levels. It can be seen that the students' skill level is better than before the implementation of reading habit with the help of picture story books. Then students' communication skills also increase. So the increase in linguistic intelligence of the second grade students of SD Negeri Duduwetan after the application of reading habits before learning.